A new method for studying the problem of optimal dynamic measurement in the presence of observation interference. (December 2021) - Alexandr, Shestakov; Sophiya, Zagrebina; Minzilya, Sagadeeva; Evgeniy, Bychkov; Natalya, Solovyova; Nikita, Goncharov; Georgy, Sviridyuk
Abstract: This paper describes a new method for studying the problem of optimal dynamic measurement in the framework of a new paradigm of dynamic measurements. This paradigm is based, on the one hand, on the automatic control model theory to describe the model of a measuring transducer, and on the other hand, on optimal control theory for Leontief-type equations. The focus is on processing experimental data, which make it possible to pass from a stochastic model to a deterministic one. In the first part, a stochastic mathematical model of a measuring device is described and conditions for the existence of an optimal measurement are given. In the second part, the algorithm of processing experimental data for constructing the deterministic part of the observation at the preliminary stage is described. Therefore, methods and algorithms for solving deterministic problems can be applied to the model in the presence of "noise".